2012
DOI: 10.1186/1479-5876-10-222
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of circulating tumor cell analysis in colorectal cancer patients

Abstract: ObjectiveThe aim of this study was to assess the prognostic and predictive values of circulating tumor cell (CTC) analysis in colorectal cancer patients.Patients and methodsPresence of CTCs was evaluated in 60 colorectal cancer patients before systemic therapy - from which 33 patients were also evaluable for CTC analysis during the first 3 months of treatment - through immunomagnetic enrichment, using the antibodies BM7 and VU1D9 (targeting mucin 1 and EpCAM, respectively), followed by real-time RT-PCR analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 13 publications
3
43
3
1
Order By: Relevance
“…12 Another study provided evidence of a strong correlation between CTC detection and radiographic disease progression in patients receiving chemotherapy for CRC. 15 In agreement with these findings, a recent meta-analysis demonstrated that the detection of CTCs in patients with resectable CRC liver metastases is associated with poor survival. 23 Finally, serum CEA levels did not correlate with high tumor burden in the liver, however the statistical power to verify this relationship may not have enough strength.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…12 Another study provided evidence of a strong correlation between CTC detection and radiographic disease progression in patients receiving chemotherapy for CRC. 15 In agreement with these findings, a recent meta-analysis demonstrated that the detection of CTCs in patients with resectable CRC liver metastases is associated with poor survival. 23 Finally, serum CEA levels did not correlate with high tumor burden in the liver, however the statistical power to verify this relationship may not have enough strength.…”
Section: Discussionmentioning
confidence: 56%
“…[12][13][14] In addition, a strong correlation between detection of CTCs and radiographic disease progression in patients receiving chemotherapy for CRC has been demonstrated. 15 We hypothesized that the quantity of baseline CTCs is associated with the tumor burden in the liver in patients with a novel stage IV CRC diagnosis. The study demonstrates that CTC quantity correlates with high tumor burden in the liver and elevated serum CEA levels in stage IV CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have shown that CTC detection is an important prognostic factor in patients with mCRC. [10][11][12][13][14] High levels of CTCs are correlated with worse prognosis in breast cancer and their decrease after treatment are related to better survival. 15 More recently, liquid biopsy technology, such as CTCs, have shown to be able to provide real time information about the tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted studies demonstrating that immunomagnetic enrichment followed by real-time PCR analysis of the tumor-associated genes keratin 19 (KRT19) , mucin 1 (MUC1) , epithelial cell adhesion molecule (EPCAM) , carcinoembryonic antigen-related cell adhesion molecule 5 (CEACAM5) and survivin (BIRC5) can be used to detect CTC as independent predictors of progression-free survival (PFS) in patients with pancreatic [10] and colon cancer [11]. …”
Section: Introductionmentioning
confidence: 99%